The transcription factor NFAT5 is required for cyclin expression and cell cycle progression in cells exposed to hypertonic stress. - Katherine Drews-Elger (Public Library of Science (PLoS), 2009)
Background Hypertonicity can perturb cellular functions, induce DNA damage-like responses and inhibit proliferation. The transcription factor NFAT5 induces osmoprotective gene products that allow cells to adapt to sustained hypertonic conditions. Although it is known that NFAT5-deficient lymphocytes and renal medullary cells have reduced proliferative capacity and viability under hypertonic stress, less is understood about the contribution of this factor to DNA damage responses and cell cycle regulation. Methodology/principal findings We have generated conditional knockout mice to obtain NFAT5(-/-) T lymphocytes, which we used as a model of proliferating cells to study NFAT5-dependent responses. We show that hypertonicity triggered an early, NFAT5-independent, genotoxic stress-like response with induction of p53, p21 and GADD45, downregulation of cyclins, and cell cycle arrest. This was followed by an NFAT5-dependent adaptive phase in wild-type cells, which induced an osmoprotective gene expression program, downregulated stress markers, resumed cyclin expression and proliferation, and displayed enhanced NFAT5 transcriptional activity in S and G2/M. In contrast, NFAT5(-/-) cells failed to induce osmoprotective genes and exhibited poorer viability. Although surviving NFAT5(-/-) cells downregulated genotoxic stress markers, they underwent cell cycle arrest in G1/S and G2/M, which was associated with reduced expression of cyclins E1, A2 and B1. We also show that pathologic hypertonicity levels, as occurring in plasma of patients and animal models of osmoregulatory disorders, inhibited the induction of cyclins and aurora B kinase in response to T cell receptor stimulation in fresh NFAT5(-/-) lymphocytes. Conclusions/significance We conclude that NFAT5 facilitates cell proliferation under hypertonic conditions by inducing an osmoadaptive response that enables cells to express fundamental regulators needed for cell cycle progression.